Optimization of The Concentration of Precipitation Reagent in Cyclamate Analysis and Determination of Cyclamate Contents in Jamu - Sistia Asfa Fiqrotinnisa; Mohammad Alauhdin (Journal of Science and Technology Research for Pharmacy, 2023)
: Sodium cyclamate is one of the food additives sweeteners that are often added to food products including jamu. It has a low price and a taste 30 - 50 times sweeter than natural sugar. It is known that excessive & longterm use of sodium cyclamate can cause adverse health effects. Currently, the standard method used to detect the presence of cyclamate refers to the precipitation method of SNI 01-2893. However, the level of sensitivity of the method is unknown. This study aims to determine the sensitivity of the precipitation method of SNI 01-2893, as well as to optimize reagents that have better sensitivity to be used as a reference for cyclamate precipitation reagents and applied to measure cyclamate in jamu. The determination the method’s sensitivity is based on the smallest concentration of cyclamate standard that can be detected by the method. Optimization of the precipitation reagent was carried out on 6 variations of precipitation reagent concentration to obtain a new formula that has a better sensitivity than the SNI 01-2893 method. Jamu samples were tested using the new optimized reagent formula. The result showed the detection limit of the of SNI 01-2893 method is 5 ppm. Optimization of the precipitation reagent formula with the composition of HCl 10%, BaCl2 10%, and NaNO2 20% showed as the highest sensitivity. It was marked by an increase in the amount of precipitate formed and had a detection limit of up to 0.9 ppm. Based on testing using the new reagent, 9 out of 10 jamu samples were positive for cyclamate. The cyclamate levels of the 9 jamu samples were measured using the spectrophotometric method, the results showed cyclamate levels are in the range of 4.3 - 6.32 mg/kg sample and meeting BPOM requirements.